2005
DOI: 10.1542/peds.2004-1463
|View full text |Cite
|
Sign up to set email alerts
|

Oral Probiotics Reduce the Incidence and Severity of Necrotizing Enterocolitis in Very Low Birth Weight Infants

Abstract: Infloran as probiotics fed enterally with breast milk reduces the incidence and severity of NEC in VLBW infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
409
4
23

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 576 publications
(453 citation statements)
references
References 38 publications
17
409
4
23
Order By: Relevance
“…It seems unlikely that differences in dosage are the cause as the log units of probiotic germs were highest in our study. Moreover, the dosage did not directly correlate with the effect (here: 4 × 10 9 vs. Lin et al (15): 2 × 10 9 /kg and Hoyos (16): 0.25 × 10 9 ). Also, the smaller effect in our study may be accounted for by practice differences between different units.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…It seems unlikely that differences in dosage are the cause as the log units of probiotic germs were highest in our study. Moreover, the dosage did not directly correlate with the effect (here: 4 × 10 9 vs. Lin et al (15): 2 × 10 9 /kg and Hoyos (16): 0.25 × 10 9 ). Also, the smaller effect in our study may be accounted for by practice differences between different units.…”
Section: Discussionmentioning
confidence: 58%
“…Some studies suggest that probiotics also reduce the severity of NEC. Using Infloran (Laboratorio Farmaceutico), Lin et al (15) showed that 6/10 NEC cases in the control group, but only 0/2 in the study group, were Bell stage 3. Bin-Nun et al (18) also reported a significant reduction in NEC severity using ABCDophilus (Solgar).…”
Section: Discussionmentioning
confidence: 99%
“…In 1999, Hoyos and colleagues reported the outcome of a cohort study, in which, probiotic administration was associated with a reduction in the incidence of necrotizing enterocolitis [53]. Between 2003 and 2006, several randomised studies reported a reduction in the incidence of NEC among preterm babies recruited to probiotic trials (and receiving the probiotic intervention) though not all these studies were designed to evaluate NEC as a primary outcome [54][55][56][57][58][59]. The first meta-analysis combining these results was published in 2007 and concluded that probiotics might reduce the risk of NEC in preterm babies born less 33 weeks gestation [60].…”
Section: Probiotics For the Prevention Of Necmentioning
confidence: 99%
“…33,34 Generally, prematurity, enteral feeding, ischaemia and bacterial colonisation are the most common risk factors for the development of NEC. [35][36][37][38] The pathogenesis of NEC in neonates born to HIV-infected mothers has not been clearly elucidated. Some described contributing factors include maternal antiretroviral treatment, maternal sepsis and immunological abnormalities.…”
Section: Necrotising Enterocolitismentioning
confidence: 99%